2010
DOI: 10.1029/2009gc002558
|View full text |Cite
|
Sign up to set email alerts
|

Duration, magnitude, and frequency of subaerial volcano deformation events: New results from Latin America using InSAR and a global synthesis

Abstract: [1] We combine new observations of volcano deformation in Latin America with more than 100 previous deformation studies in other areas of the world to constrain the frequency, magnitude, and duration of subaerial volcano deformation events. We discuss implications for eruptive hazards from a given deformation event and the optimum repeat interval for proposed InSAR satellite missions. We use L band (23.6 cm wavelength) satellite-based interferometric synthetic aperture radar (InSAR) to make the first systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 144 publications
7
128
1
Order By: Relevance
“…Observations of precursory deformation with InSAR are relatively rare at explosive volcanoes, which has been attributed to the characteristics of the magma reservoir (Chaussard and Amelung, 2012;Ebmeier et al, 2013), a lack of pressurization (Chaussard et al, 2013), the steep topography (Pinel et al, 2011) or temporal aliasing (Fournier et al, 2010). The short temporal baseline and high resolution of our satellite imagery, in combination with a high quality DEM, reduces errors typically associated when using standard resolution InSAR in this type of terrain (Pinel et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Observations of precursory deformation with InSAR are relatively rare at explosive volcanoes, which has been attributed to the characteristics of the magma reservoir (Chaussard and Amelung, 2012;Ebmeier et al, 2013), a lack of pressurization (Chaussard et al, 2013), the steep topography (Pinel et al, 2011) or temporal aliasing (Fournier et al, 2010). The short temporal baseline and high resolution of our satellite imagery, in combination with a high quality DEM, reduces errors typically associated when using standard resolution InSAR in this type of terrain (Pinel et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…We exploit the radar data interferometrically (InSAR), a method now used routinely to analyze large scale deformation at many volcanoes (Fournier et al, 2010;Ebmeier et al, 2013), and allowing the identification of the depths and geometries of volcanic magma chambers (Dzurisin, 2007). Recent studies have also revealed the importance of both timeliness and spatial resolution when identifying processes associated with basaltic eruptions (Bagnardi et al, 2013;Richter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Point source or penny-shaped cracks [Mogi, 1958;Fialko et al, 2001] produce circular deformation patterns which are inconsistent withthe elongated fringe pattern observed. Models of dike intrusion, including that proposed by Fournier et al [2010], are dominated by horizontal motion and typically have two lobes [Okada, 1985], providing a poor fit.…”
Section: Deformation Sourcementioning
confidence: 99%
“…In the past decade a great progress has been made with geodetic measurements, especially near volcanoes. However, it has been shown using InSAR that the deformation near Láscar volcano is considerable less than other zones within the Andes (Pritchard and Simons, 2004;Henderson y Pritchard, 2013;Fournier et al, 2010). Therefore, it is likely that the source of the inferred velocity change can be due to fluid motion in a very local region, and by small amounts, and can not be detected on a larger scale as observed with InSAR.…”
Section: Resultsmentioning
confidence: 86%